A sulfur coordination polymer with wide bandgap semiconductivity formed from zinc(II) and 5‐methylsulfanyl‐1, 3, 4‐thiadiazole‐2‐thione. Issue 9 (8th August 2019) - Zhang, Jun; Ma, Xiaofan; Kong, Weili; Xie, Fazhi; Yuan, Shizhen; Song, Xiaojie; Lu, Zhansheng; Xuan, Xiaopeng
Abstract : A sulfur coordination polymer constructed from Zn 2+ ions and 5‐methylsulfanyl‐1, 3, 4‐thiadiazole‐2‐thione possesses high thermal and chemical stability and a linear temperature dependence of the bandgap from room temperature to 270 °C. Further investigation revealed that the bandgap changes sharply in ammonia, but only fluctuates slightly in other solvents, indicating its promising application as a selective sensor. Abstract : The sulfur coordination polymer catena ‐poly[zinc(II)‐μ2 ‐bis[5‐(methylsulfanyl)‐2‐sulfanylidene‐2, 3‐dihydro‐1, 3, 4‐thiadiazol‐3‐ido‐κ 2 N 3 : S ]], [Zn(C3 H3 N2 S3 )2 ] n or [Zn2 MTT4 ] n, constructed from Zn 2+ ions and 5‐methylsulfanyl‐1, 3, 4‐thiadiazole‐2‐thione (HMTT), was synthesized successfully and structurally characterized. [Zn2 MTT4 ] n crystallizes in the tetragonal space group I (No. 82). Each MTT − ligand (systematic name: 5‐methylsulfanyl‐2‐sulfanylidene‐2, 3‐dihydro‐1, 3, 4‐thiadiazol‐3‐ide) coordinates to two different Zn II ions, one via the thione group and the other via a ring N atom, with one Zn II atom being in a tetrahedral ZnS4 and the other in a tetrahedral ZnN4 coordination environment. These tetrahedral ZnS4 and ZnN4 units are alternately linked by the organic ligands, forming a one‐dimensional chain structure along the c axis. The one‐dimensional chains are further linked via C—H…N and C—H…S hydrogen bonds to form a three‐dimensional network adopting an ABAB ‐style arrangement that lies along both the a and b axes. The three‐dimensional Hirshfeld surface analysis and two‐dimensional (2D) fingerprint plots confirm the major interactions as C—H…S hydrogen bonds with a total of 35.1%, while 7.4% are C—H…N hydrogen‐bond interactions. [Zn2 MTT4 ] n possesses high thermal and chemical stability and a linear temperature dependence of the bandgap from room temperature to 270 °C. Further investigation revealed that the bandgap changes sharply in ammonia, but only fluctuates slightly in other solvents, indicating its promising application as a selective sensor.